Massive Localized Lymphedema in an Unreported Location (Retroperitoneum) - Dilek Ertoy Baydar (Diagnostic Pathology, 2018)
Abstract Background Massive localized lymphedema (MLL) is a non-neoplastic benign soft tissue lesion that may be confused with sarcomas or other neoplastic proliferations both clinically and morphologically. Most occur in morbidly obese adults on the lower extremities. The objective of this article is to document a case of MLL in the retroperitoneal cavity which is a previously unreported site for this lesion, and to highlight its unusual clinical features. Case presentation The patient was a non-obese male who had undergone major abdominal surgery due to bladder extrophy 17 years ago. Abdominal ultrasonography detected a large incidental mass in the right renal sinus during his investigation for nephrolithiasis. The lesion extending from renal pelvis down to pelvis was resected and its histopathological findings were compatible with massive localized lymphedema. Conclusions Retroperitoneum has to be added to the list of locations that MLL can be found. Liposarcoma will be a challenging differential diagnosis when the lesion is encountered in an unusual site.